Natural killer T cell defects in multiple myeloma and the impact of lenalidomide therapy. (January 2014) - Chan, A. C.; Neeson, P.; Leeansyah, E.; Tainton, K.; Quach, H.; Prince, H. M.; Harrison, S. J.; Godfrey, D. I.; Ritchie, D.; Berzins, S. P.
Summary The causes of multiple myeloma (MM) remain obscure and there are few known risk factors; however, natural killer T (NKT) cell abnormalities have been reported in patients with MM, and therapeutic targeting of NKT cells is promoted as a potential treatment. We characterized NKT cell defects in treated and untreated patients with MM and determined the impact of lenalidomide therapy on the NKT cell pool. Lenalidomide is an immunomodulatory drug with co‐stimulatory effects on NKT cells in vitro and is an approved treatment for MM, although its mode of action in that context is not well defined. We find that patients with relapsed/progressive MM had a marked deficiency in NKT cell numbers. In contrast, newly diagnosed patients had relatively normal NKT cell frequency and function prior to treatment, although a specific NKT cell deficiency emerged after high‐dose melphalan and autologous stem cell transplantation (ASCT) regimen. This also impacted NK cells and conventional T cells, but the recovery of NKT cells was considerably delayed, resulting in a prolonged, treatment‐induced NKT cell deficit. Longitudinal analysis of individual patients revealed that lenalidomide therapy had no in‐vivo impact on NKT cell numbers or cytokine production, either as induction therapy, or as maintenance therapy following ASCT, indicating that its clinical benefits in this setting are independent of NKT cell modulation.